A Simple Allergist-Led Intervention Improves Resident Training in Anaphylaxis. (21st February 2016) - Jongco, Artemio M.; Bina, Sheila; Sporter, Robert J.; Cavuoto Petrizzo, Marie A.; Kaplan, Blanka; Kline, Myriam; Schuval, Susan J.
Abstract : Physicians underrecognize and undertreat anaphylaxis. Effective interventions are needed to improve physician knowledge and competency regarding evidence-based anaphylaxis diagnosis and management (ADAM). We designed and evaluated an educational program to improve ADAM in pediatrics, internal medicine, and emergency medicine residents from two academic medical centers. Anonymous questionnaires queried participants' demographics, prior ADAM clinical experience, competency, and comfort. A pretest assessing baseline knowledge preceded a 45-minute allergist-led evidence-based presentation, including practice with epinephrine autoinjectors, immediately followed by a posttest. A follow-up test assessed long-term knowledge retention twelve weeks later. 159 residents participated in the pretest, 152 participated in the posttest, and 86 participated in the follow-up test. There were no significant differences by specialty or site. With a possible score of 10, the mean pretest score (7.31 ± 1.50) was lower than the posttest score (8.79 ± 1.29) and follow-up score (8.17 ± 1.72) (P < 0.001 for both). Although participants' perceived confidence in diagnosing or managing anaphylaxis improved from baseline to follow-up (P < 0.001 for both), participants' self-reported clinical experience with ADAM or autoinjector use was unchanged. Allergist-led face-to-face educational intervention improves residents' short-term knowledge and perceived confidence in ADAM. Limited clinical experience or reinforcement contributes to the observed decreased knowledge.